Symmetry and conserved quantities of discrete generalized Birkhoffian system - 张克军 方建会 李燕 (Chinese physics B, 2010)
The Noether symmetry, the Mei symmetry and the conserved quantities of discrete generalized Birkhoffian system are studied in this paper. Using the difference discrete variational approach, the difference discrete variational principle of discrete generalized Birkhoffian system is derived. The discrete equations of motion of the system are established. The criterion of Noether symmetry and Mei symmetry of the system is given. The discrete Noether and Mei conserved quantities and the conditions for their existence are obtained. Finally, an example is given to show the applications of the results.